The Effect of Shred Injuries Soccer on General Injuries of Futsal Athletes - Achmad Fauzan Alfaz; Prisca Widiawati; Muhammad Putra Ramadhan (Physical Education Departement of University PGRI Jombang, 2025)
This study aims to determine the effect of shred injuries soccer on the risk of general injuries in Malang State University (UM) futsal club athletes. This research method uses an experimental approach with the subject of the UM futsal club which will take part in the Euro 2024 regional orphan competition. The results of this study indicate that the results of the FMS Funcional Movement Screen test) using shred injuries on UM futsal club athletes obtained an average pre-test value of 16.27, while during the post-test the average value was 17.90. The pre-test normality test result is 0.074 indicating normal data distribution, while the post-test obtained a value of 0.023 which indicates abnormal data distribution, so that comparative analysis can be carried out using the Wilcoxon T-test to determine the effect of the treatment given. The results of the analysis with the Wilcoxon test showed a significant effect between the pre-test and post-test values with a p value = 0.008. So it can be concluded that this study has a significant effect on the application of shred injuries to general injuries in UM futsal club athletes